Lung function in young adulthood: differences between males and females with asthma - Ida Mogensen; Jenny Hallberg; Lena Palmberg; Sandra Ekström; Antonios Georgelis; Erik Melén; Anna Bergström; Inger Kull (ERJ Open Research, 2022)
Background There are phenotypic differences in asthma in males and females. Differences in lung function between the sexes at the peak lung function level in young adulthood are so far not directly addressed. The aim of the present study was to assess lung function in early adulthood in males and females depending on asthma onset and remission. Methods Participants were included from the population-based birth cohort BAMSE and classified as having: never asthma, childhood asthma in remission, adolescent onset asthma or persistent asthma. Pre- and post-bronchodilator lung function (in Z-score) and lung clearance index (LCI) were measured at age 24 years. Lung function was compared stratified for sex between the never asthma and asthma groups univariately and in multiple linear regression analyses adjusted for maternal and paternal asthma, maternal smoking during pregnancy, secondary smoking, daily smoking, early respiratory syncytial virus infection, traffic pollution, childhood allergic sensitisation, and body mass index at age 24 years. Results All asthma phenotypes were associated with a lower forced expiratory volume in 1 s (FEV1)/forced vital capacity (FVC) post-bronchodilation at 24 years. This was most pronounced in males with persistent asthma compared to males with never asthma (regression coefficient: −0.503; 95% CI: −0.708– −0.298). Childhood asthma (in remission or persistent) was associated with a lower FEV1. After adjustment, the associations remained significant for males. For females, the significant associations with lower FEV1 and FEV1/FVC remained only for subjects with asthma in remission. Persistent asthma was associated with higher LCI in females. Conclusions In females, in contrast to males, the association between asthma and lower lung function was attenuated after adjustment for known risk factors.